Diversidad de arqueas en ecosistemas estuarino-lagunares tropicales y subtropicales. Una síntesis: Archaea in tropical coastal ecosystems - Torres-Alvarado, Marìa del Rocìo; Calva-Benítez, Laura Georgina; Maldonado-Vela , Neivy Betsabet (HIDROBIOLÓGICA, 2022)
Background. Tropical and subtropical estuarine ecosystems are among the most productive ecosystems on the planet, their seasonal fluctuations, their permanent or ephemeral connection with the ocean and freshwater discharges, generate a high biodiversity that provides numerous ecosystem services. In these ecosystems, biodiversity research has focused on macro-organisms and less attention has been paid to prokaryotes, particularly the archaea group. Goal. Based on a bibliographic review of the Archaea Domain in estuaries, coastal lagoons and mangroves located in tropical and subtropical zones, to provide a synthesis of the factors that influence the presence and distribution of archaea in these ecosystems and the role they play in biogeochemical cycles. Methods. A search was made of the articles published with the keywords Archaea + tropical coastal ecosystems and Archaea + subtropical coastal ecosystems. Results. The analysis of the environmental sequences obtained, from molecular techniques, in studies of the diversity of prokaryotes in coastal lagoons, estuaries and tropical and subtropical mangroves, have revealed a high diversity of archaea belonging mainly to methanogens and anaerobic methanotrophs (Phyla Euryarchaeota), ammonium-oxidizing archaea (Thaumarchaeota) and representatives of the Superphyllum Asgard. These groups can potentially participate in the carbon, nitrogen, and sulfur cycles, in aerobic or anaerobic conditions, with heterotrophic or autotrophic metabolisms, and their abundance and distribution are related to the physicochemical conditions of the ecosystems. Conclusions. The diversity of Archaea in tropical and subtropical coastal ecosystems is greater than previously recorded. These microorganisms play a vital role in various biogeochemical cycles as well as climate change